ANALYSIS OF FACTORS AFFECTING LIFE EXPECTANCY IN NORTH SUMATRA PROVINCE USING LASSO AND ADAPTIVE LASSO - Nasution, Rini Halila; Tamimi, Alifiyani (Jurnal Lebesgue : Jurnal Ilmiah Pendidikan Matematika, Matematika dan Statistika, 2024)
Life expectancy is a measure used to evaluate the government's effectiveness in enhancing the overall well-being and health of the population. The life expectancy of a town is impacted by the educational attainment of its residents. LASSO regression is a variant of linear regression that incorporates an extra penalty term into the cost function. adjustable LASSO Regression is a modified version of this technique that incorporates adjustable weighting variables for each coefficient, enhancing its effectiveness.Multicollinearity, a condition of strong correlation between predictor variables, can complicate the identification of independent variables that have a significant impact. The LASSO and Adaptive LASSO are variable selection strategies used in multiple linear regression situations. The LASSO and Adaptive LASSO techniques are effective for identifying important variables and establishing the link between independent and dependent variables